2020
DOI: 10.1080/02109395.2020.1748843
|View full text |Cite
|
Sign up to set email alerts
|

Research on numerical cognition in Latin American countries (Investigación sobre cognición numérica en países latinoamericanos)

Abstract: Towards evidenced-guided reforms on the mathematics educationOver the last few decades, Latin America and the Caribbean (LAC) countries have increased their spending on education (Bertoni et al., 2018) significantly. Governments have raised the salaries of teachers to signal the importance of education and to attract more students to select the teaching profession. Likewise, many reforms and programmes have been introduced to improve learning, especially in disadvantaged schools and areas. The available data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Pairwise comparisons indicated that 5 th graders' scores were higher than those of 4 th and 3 rd graders, and 4 th graders' scores were higher than those of 3 rd graders. There also was a significant main effect of operation, F (2,1321) =1085.34, p<0.001, ⴄ p 2 =0.26. Pairwise comparisons indicated that addition operations were solved better than subtraction and multiplication operations and that subtraction operations were solved better than multiplication operations.…”
Section: Multiplicationmentioning
confidence: 92%
See 1 more Smart Citation
“…Pairwise comparisons indicated that 5 th graders' scores were higher than those of 4 th and 3 rd graders, and 4 th graders' scores were higher than those of 3 rd graders. There also was a significant main effect of operation, F (2,1321) =1085.34, p<0.001, ⴄ p 2 =0.26. Pairwise comparisons indicated that addition operations were solved better than subtraction and multiplication operations and that subtraction operations were solved better than multiplication operations.…”
Section: Multiplicationmentioning
confidence: 92%
“…1 For this reason, many countries have increased investments in basic mathematical education. [1][2][3] Despite increased international recognition and higher investments in mathematical education, mathematical achievement in several countries remains a cause for concern. 4 This is especially the case in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to and beyond being crucial for everyday life activities such as reading the clock, evaluating change, and measuring ingredients specified in a recipe, numerical and mathematical abilities also predict an individual's life prospects such as employment, income, and social as well as psychological well-being, even after controlling for reading abilities (Bynner & Parsons, 2005;Ritchie & Bates, 2013). Not surprisingly, numerical and mathematical abilities have thus been considered important economic factors in our post-industrial societies (Beddington et al, 2008;Haase et al, 2020;Kotzé, 2019). Mathematics is an important predictor of scientific and technological development, which seems important for success in competitive global economies.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematics is an important predictor of scientific and technological development, which seems important for success in competitive global economies. For this reason, many countries have increased investments in basic mathematical education (Beddington et al, 2008;Haase et al, 2020;Kotzé, 2019). Despite increased international recognition and higher investments in mathematical education, mathematical achievement in several countries remains a cause for concern (Haase & Krinzinger, 2019).…”
Section: Introductionmentioning
confidence: 99%